Pembuatan Feeds Instagram Sebagai Media Promosi Untuk Menciptakan Brand Awareness Pada UMKM Kimbab Foodnaku di Kota Malang - Salsabila Fitri Wijaya; Heru Utomo; Dwi Sudjanarti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to design Instagram feeds design as a promotional media in an effort to create brand awareness at Kimbab Foodnaku MSMEs in Malang City. The problems faced by these MSMEs are the limited range of promotion and the appearance of the @foodnaku_ Instagram account does not have a consistent visual design in the use of colors, typography, and low image quality. This research uses the spiral model action research method with 2 cycles which include the stages of planning, action, observation, and reflection. Data were collected through interviews, observations, documentation, and distributing questionnaires to 20 respondents consisting of business owners, design experts, marketing experts, and potential customers. Design effectiveness was measured through four levels. The results showed that the feeds design created with Adobe Illustrator proved to be very effective and worth publishing as a promotional media. The design is able to increase consumer attention, interest, and understanding of the product and significantly strengthen brand identity.